The Protective Effect of Taurine and Curcumin on Autophagy-Related Genes in the Oocytes of the Mouse Treated with Acrylamide - Maryam Davari Zanjani; Zahra Khodabandeh; Mohammad Amin Edalatmanesh (Iranian Journal of Medical Sciences)
Background: Autophagy is also essential for both male and female infertility since it controls the development of germ cells and reproductive organs. This study aimed to investigate the effects of taurine and curcumin on the expression of genes related to autophagy in acrylamide-treated mice. Methods: In 2022, this experimental study was conducted at the Shiraz University of Medical Sciences, Stem Cells Technology Research Centre. Forty-eight mice were randomly assigned to eight groups (control, curcumin 200 mg/Kg, taurine 150 mg/Kg, acrylamide 50 mg/Kg, acrylamide+curcumin 100 mg/Kg, acrylamide+curcumin 200, acrylamide+taurine 75 mg/Kg, acrylamide+taurine 150 mg/Kg). Finally, oocyte characteristics and gene expression were determined in each group using one-way analysis of variance (ANOVA) by SPSS 25 and GraphPad 9, respectively. P<0.05 was conducted statistically significant. Results: A significant decrease was observed in several oocytes in the acrylamide group compared to the control group (P<0.001). The expression levels of light chain 3 (LC3), autophagy-related gene (ATG)12, ATG5, and Beclin1 significantly increased in the acrylamide compared to the control group. A significant increase in the number of oocytes was observed in the taurine group compared to the control. The expression levels of LC3, ATG12, ATG5, and Beclin1 significantly decreased in the acrylamide+taurine (150 mg/Kg) compared to the acrylamide group. Conclusion: The acrylamide negatively impacts oocyte viability and causes the higher expression of autophagy-related genes. Taurine may encourage the fusion of autophagosomes with lysosomes by removing autophagic obstruction, potentially accelerating autophagy and protecting against oxidative stress. Taurine is more effective than curcumin at reducing the harmful effects of acrylamide. As a result, taurine can be proposed as a potential treatment drug for acrylamide-induced infertility.